Design and build online citizens complaint system in Labuhanbatu using Waterfall Method - Munandar, Aris; Irmayani, Deci; Juledi, Angga Putra (Politeknik Ganesha Medan, 2022)
The rapid development of ICT has opened up opportunities for citizens to submit opinions and complaints to the Government, which facilities are guaranteed by law. The provision of these facilities is in the form of implementing e-Government. The government must provide an application that is Government to Citizens/Consumers (G2C) which aims to bring the government closer to the community interactively through access channels that can be reached by the community. Labuhanbatu is a district located in North Sumatra Province with a population of 493,899 people. However, until now there is no facility for the public to submit aspirations or complaints based on e-Government applications. This study aims to create a web-based online application for aspiration and complaint services for the people of Labuhanbatu Regency. This application is called LAPO, which stands for Online Aspirations and Complaints Service. The method used in this research is the Waterfall model. This research has succeeded in creating a web-based online aspiration and complaint service system for Labuhanbatu residents that shows the compatibility between the expected results and the actual results. The results of the study have proven that to design and build this system, the following stages are carried out: analyzing system requirements, system design, implementing the system, and conducting system testing. With this research, it is hoped that it can become one of the e-Government applications for aspiration and complaint services that can be used by the Labuhanbatu Regency Government easily and with low infrastructure costs by utilizing existing human resources.